2019
DOI: 10.1177/0269881119826594
|View full text |Cite
|
Sign up to set email alerts
|

Greater empathy in MDMA users

Abstract: Background: 3,4-Methylenedioxymethamphetamine (MDMA) is widely known for its positive acute effects on social behaviour, such as increasing empathy, whilst also attenuating the negative impact of social exclusion. However there is a scarcity of research that investigates the long-term impact of recreational MDMA use on these fundamental social processes. Method: Sixty-seven individuals were split into three groups based on their drug-use history: poly-drug MDMA users (n = 25), poly-drug users who do not use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…It has been reported that recreational MDMA users showed increased cognitive, but not emotional, empathy compared to controls on the MET and the MASC (87, 88). Furthermore, they exhibited less-self-serving behavior on a money allocation task played with a stranger (87).…”
Section: Long-lasting Effects In Healthy Participantsmentioning
confidence: 99%
“…It has been reported that recreational MDMA users showed increased cognitive, but not emotional, empathy compared to controls on the MET and the MASC (87, 88). Furthermore, they exhibited less-self-serving behavior on a money allocation task played with a stranger (87).…”
Section: Long-lasting Effects In Healthy Participantsmentioning
confidence: 99%
“…Wunderli at el (140) and Carlyle et al (139) both showed that chronic MDMA use was not associated with changes of the emotional empathy domain of the MET.…”
Section: Emotional Empathymentioning
confidence: 99%
“…The valence-dependent acute effects of MDMA were found in an emotional face recognition task (132,133) and the RMET (136), whereas cognitive empathy performance measured with the MET was not affected by acute MDMA intake (133,137,138). In contrast to the acute effects, two studies have recently shown that chronic users of MDMA exhibit superior cognitive empathy compared to controls when assessed with complex emotionally laden scenes from the MET (139,140). However, as lower cognitive empathy was clearly correlated with higher MDMA concentrations in hair, one of the author groups concluded that the differences at the group level were likely explained by higher social affiliation motivations of the users, while at higher chronic doses MDMA might nevertheless impair cognitive empathy (140).…”
Section: Entactogenes Emotion Recognition and Cognitive Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent studies, 5-HT transmission is also involved in a series of social behaviors such as social interaction (Walsh et al, 2018), social reward and aggression (Dolen, Darvishzadeh, Huang, & Malenka, 2013). Regarding empathy, a recent study revealed an association between the salivary 5-HT levels and the empathic abilities of people (Matsunaga et al, 2017); a polymorphism in the promoter region of the serotonin transporter gene has been linked to individual differences in empathy (Gyurak et al, 2013); MDMA (±3,4-methylenedioxymethamphetamine, better known as the recreational drug “ecstasy’’), which is well known to stimulate a feeling of closeness and empathy in its users (Carlyle et al, 2019), had been confirmed to robustly increase the release of 5-HT in an activity-independent manner (Heifets & Malenka, 2016). In animal studies, Kim, et al found that microinjection of 5-HT into the anterior cingulate cortex (ACC) impaired vicarious fear and altered the regularity of neural oscillations in mice (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%